STUDI KRITIS BAHAN AJAR PAI DALAM MATERI MERAIH KESUKSESAN DENGAN SEMANGAT MENCARI ILMU KELAS IX DI SMP ISLAM AL AZHAR 7 KOTA SUKABUMI - Muhammad Helmi Alfian; Siti Qomariyah; Irawati; Dwi Suryani Kurniawan; Siti Sopa Rismawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to critically analyze the teaching materials of Pendidikan Agama Islam on the topic Achieving Success with the Spirit of Seeking Knowledge for ninth-grade students at SMP Islam Al Azhar 7 Kota Sukabumi. The focus of this study includes the analysis of learning objectives, learning materials, learning methods, learning evaluation, learning resources, and teaching materials as a whole. This study employed a qualitative approach using a critical study method. Data were collected through documentation studies of the teaching modules used in the learning process. The results of the study indicate that, in general, the teaching materials have fulfilled the main components of learning, including learning objectives, learning materials, learning methods, evaluation, and learning resources, which are systematically arranged in accordance with the characteristics of the Merdeka Curriculum. The learning objectives have covered cognitive, affective, and psychomotor domains; the learning materials are relevant to Islamic values and students’ developmental characteristics; the learning methods have reflected active learning; the evaluation has covered knowledge, attitudes, and skills; and the learning resources have utilized the Qur'an, hadith, textbooks, and teaching modules. However, the analysis also reveals several weaknesses, such as learning objectives that are not fully operational, learning materials that are not yet optimally contextualized with the digital era, evaluations that do not entirely use measurable assessment rubrics, and limited utilization of digital media and learning resources. Based on the findings, it can be concluded that the Islamic Religious Education teaching materials on the topic Achieving Success with the Spirit of Seeking Knowledge are appropriate for use in the learning process, but still require further development to become more contextual, innovative, practical, and relevant to students’ needs in the modern era.